Modulatory effect of MG-132 proteasomal inhibition on boar sperm motility during in vitro capacitation - Hackerova, Lenka; Klusackova, Barbora; Zigo, Michal; Zelenkova, Natalie; Havlikova, Katerina; Krejcirova, Romana; Sedmikova, Marketa; Sutovsky, Peter; Komrskova, Katerina; Postlerova, Pavla; Simonik, Ondrej (Frontiers in Veterinary Science, 2023)
A series of biochemical and biophysical changes during sperm capacitation initiates various signaling pathways related to protein phosphorylation leading to sperm hyperactivation, simultaneously with the regulation of proteasomal activity responsible for protein degradation and turnover. Our study aimed to unveil the role of the proteasome in the regulation of boar sperm motility, hyperactivated status, tyrosine phosphorylation, and total protein ubiquitination. The proteolytic activity of the 20S proteasomal core was inhibited by MG-132 in concentrations of 10, 25, 50, and 100 μM; and monitored parameters were analyzed every hour during 3 hours of in vitro capacitation (IVC). Sperm motility and kinematic parameters were analyzed by Computer Assisted Sperm Analysis (CASA) during IVC, showing a significant, negative, dose-dependent effect of MG-132 on total and progressive sperm motility (TMOT, PMOT, respectively). Furthermore, proteasome inhibition by 50 and 100 µM MG-132 had a negative impact on velocity-based kinematic sperm parameters (VSL, VAP, VCL). Parameters related to the progressivity of sperm movement (LIN, STR) and ALH were the most affected by the highest inhibitor concentration (100 µM). Cluster analysis revealed that the strongest proteasome-inhibiting treatment had a significant effect (p ≤ 0.05) on the hyperactivated sperm subpopulation. The flow cytometric viability results proved that reduced TMOT and PMOT were not caused by disruption of the integrity of the plasma membrane. Neither the protein tyrosine phosphorylation profile changes nor the accumulation of protein ubiquitination was observed during the course of capacitation under proteasome inhibition. In conclusion, inhibition of the proteasome reduced the ability of spermatozoa to undergo hyperactivation; however, there was no significant effect on the level of protein tyrosine phosphorylation and accumulation of ubiquitinated proteins. These effects might be due to the presence of compensatory mechanisms or the alteration of various ubiquitin-proteasome system-regulated pathways.